A critical exploration of the barriers and opportunities to the effective management of later life depression - Hughes, Jennifer (2013)
Background: It is clear the evidence suggests later life depression remains to be a problem in our society with the severity of the condition and the impact on older individual’s physical and psychological health being well documented. However, to date policies implemented to manage depression in the older population fail to achieve their goals, yet successful treatment options are recommended on a plentiful level. Aim: To explore the barriers and opportunities to the effective management of later life depression. Method: A critical review method was utilised. A stringent research process and strategy were adopted with the development of a thematic table, in which themes were developed, and critical analysis of the articles. Findings: Stigmatisation of the condition, and those who suffer with it, by society and healthcare professionals, along with self-stigmatisation, all act as barriers to the effective management of later life depression. Ageist attitudes remain apparent, with both society and healthcare professionals sharing the belief that depression is a natural part of ageing. Negative attitudes towards the traditional treatment options available by patients, along with the low expectation of services; contribute to the ineffective management of later life depression. Additionally limited access to specialist services creates barriers. The importance of a good patient practitioner relationship is discussed in the literature as an effective way to tackle these barriers. Moreover the use of additional community services in the management of depression is outlined, along with the incorporation of pleasant event scheduling in nursing homes. Recognising and considering individuals needs when providing treatment, is also acknowledged. Conclusion: The barriers and opportunities to the effective management of later life depression are summarised and concluded with a relevance to nursing. It is acknowledged not all these barriers can be overcome as easily as one would hope. Reflection on the dissertation process then takes place.